1994
DOI: 10.1016/0014-5793(94)01235-0
|View full text |Cite
|
Sign up to set email alerts
|

On the site by which α‐dendrotoxin binds to voltage‐dependent potassium channels: Site‐directed mutagenesis reveals that the lysine triplet 28–30 is not essential for binding

Abstract: We constructed a synthetic gene encoding the published amino acid sequence of DTx from Dendroaspis angusticeps, a ligand of voltagedependent postassium channels that facilitates neurotransmitter release. We expressed it in Escherichia coli as a fusion protein secreted in the culture medium. The recombinant DTx was generated in vitro by chemical treatment and recovered as two isoforms. One of them (rDTx), like the venom toxin, has an N-terminal pyroglutamate whereas the other (rQDTx) has a free N-terminal gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…The sense oligonucleotide (5' GGGAGCG-GAGGGTACCCATGGTACGTGACGGTTATATT 3') introduced a KpnI restriction site (underlined), and a methionine residue (bold) at position -1. Since the mature sequence of BotXIV has no methionine residue, it constitutes a unique and useful CNBr-cleavage site, as previously described for other hybrid snake toxins (Ducancel et al, 1989;Boyot et al, 1990;Hodgson et al, 1993;Danse et al, 1994). The antisense oligonucleotide (S'GGGAGCGGCAGGATCCTTATCAGCGATGGCATTTT 3') was designed to introduce a BamHI restriction site and the stop codon TAA (bold), which is efficiently recognized in E. coli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sense oligonucleotide (5' GGGAGCG-GAGGGTACCCATGGTACGTGACGGTTATATT 3') introduced a KpnI restriction site (underlined), and a methionine residue (bold) at position -1. Since the mature sequence of BotXIV has no methionine residue, it constitutes a unique and useful CNBr-cleavage site, as previously described for other hybrid snake toxins (Ducancel et al, 1989;Boyot et al, 1990;Hodgson et al, 1993;Danse et al, 1994). The antisense oligonucleotide (S'GGGAGCGGCAGGATCCTTATCAGCGATGGCATTTT 3') was designed to introduce a BamHI restriction site and the stop codon TAA (bold), which is efficiently recognized in E. coli.…”
Section: Resultsmentioning
confidence: 99%
“…BomIII (Vargas et al, 1987) presents the highest similarity (70%) with BotXIV. The system chosen to express BotXlV in E. coli was previously demonstrated to be suited to the production of soluble, correctly folded snake venom toxins (Ducancel et al, 1989;Hodgson et al, 1993;Pillet et al, 1993;Danse et al, 1994;TrCmeau et al, 1995). This system, however, had not been used to produce recombinant scorpion toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Our results may Jso help to identify which amino acids on the toxin and on the channel are necessary to confer high affinity block and -electivity. Previous approaches using both mutated channels I I0] and toxins [11] have revealed that several regions on both the toxin and channel a-subunit are required for full activity.…”
Section: Discussionmentioning
confidence: 99%
“…Substituting Arg1 by alanine resulted in a less than 10-fold decreased affinity, whereas Arg2, Leu4 and Ile6 substitution lowered the affinity 10 to 30 times. The Lys3 and Leu6 seem to be the most critical residues since mutating these amino acids resulted in a thousand times less potent toxins [30,31,35,36]. Of these residues critical for α-DTX binding, the leu4 and Ile6 are replaced by a homologous residue in APEKTx1.…”
Section: Page 7 Of 22mentioning
confidence: 99%